IGF2BP1 accelerates the aerobic glycolysis to boost its immune escape in hepatocellular carcinoma microenvironment - Ye, Xuxing; Lin, Junmei; Chen, Yanping; Wang, Xiaobo (Frontiers in Immunology, 2024)
IntroductionEnergy metabolism abnormity emerges as a crucial factor that facilitates tumorigenesis by accelerating aerobic glycolysis. However, the function of N6-methyladenosine (m6A) on hepatocellular carcinoma (HCC) aerobic glycolysis and immune escape is still unclear. Here, this investigation was intended to elucidate the regulation of m6A ‘reader’ IGF2BP1 involved in HCC aerobic glycolysis and immune escape.MethodsThe aerobic glycolysis was tested by glucose uptake, lactate, ATP generation and ECAR. The CD8+ T cell-mediated killing effect was tested by cytotoxicity, IFN-γ and granzyme B. The molecular interaction was confirmed by luciferase reporter assay, immunoprecipitation assay and chromatin immunoprecipitation (ChIP)-PCR.ResultsElevated IGF2BP1 expression was associated with poor prognosis in HCC patients. Functionally, IGF2BP1 emerged as an oncogenic factor that accelerated HCC aerobic glycolysis (glucose uptake, lactate, ATP generation and ECAR) and oxaliplatin resistance. Meanwhile, IGF2BP1 repressed the activated CD8+ T cell-mediated killing effect (cytotoxicity, IFN-γ and granzyme B) and apoptosis of HCC cells, indicating a suppressed cytotoxic T-cell response. By recognizing and binding to the m6A-modified sites on c-Myc mRNA, IGF2BP1 enhanced the stability of c-Myc mRNA, consequently upregulating c-Myc expression. In addition, transcription factor c-Myc targeted the programmed death ligand 1 (PD-L1) promoter region to strengthen its transcription.DiscussionTaken together, this study illustrates IGF2BP1 as a potential therapeutic target in HCC, aiming to disrupt the interplay between aberrant metabolism and immune escape.